2019
DOI: 10.1089/cyber.2018.0381
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Media Content on Solitary Drinking Among Korean Adults

Abstract: This study aims to provide explanations for how exposure to social media content on solitary drinking influences the frequency and quantity of solitary drinking, and posting about solitary drinking on social networking sites (SNS). An online survey was conducted with 506 Korean adults who had consumed alcohol at least once while alone in the previous year. The study showed the following results: First, exposure to social media content related to solitary drinking was positively associated with both descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…However, these results conflict with those of previous studies where solitary drinkers experienced higher levels of negative effect management and lower levels of positive effect enhancement [7][8][9], while others showed that they exhibited higher levels of positive and negative expectancies [8,9]. [4]. According to previous studies, solitary drinkers experience stress and depression more often than social drinkers do, and this is a problem that requires more attention [7,11,16].…”
Section: Factors Associated With the Frequency And Quantity Of Alcohocontrasting
confidence: 70%
See 2 more Smart Citations
“…However, these results conflict with those of previous studies where solitary drinkers experienced higher levels of negative effect management and lower levels of positive effect enhancement [7][8][9], while others showed that they exhibited higher levels of positive and negative expectancies [8,9]. [4]. According to previous studies, solitary drinkers experience stress and depression more often than social drinkers do, and this is a problem that requires more attention [7,11,16].…”
Section: Factors Associated With the Frequency And Quantity Of Alcohocontrasting
confidence: 70%
“…Social norms include society's beliefs about alcohol and drinking behaviors [4]. Behaviors related to drinking reflect the history, culture, religion, lifestyle, and racial characteristics of each ethnic group or nationality [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solitary drinking is a public health issue that should be afforded more attention, as solitary drinkers tend to drink regularly, which may lead to alcohol use disorder, while social drinkers tend not to do so on a regular basis [8]. According to previous studies, solitary drinkers experience stress and depression more often than social drinkers, a problem that should be given more attention [11,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…A society's beliefs about alcohol and drinking behaviors are part of its social norms [8]. Behaviors related to drinking reflect the history, culture, religion, lifestyle, and racial characteristics of each ethnic group or nationality [9].…”
mentioning
confidence: 99%